A study on TM Streamyx: level of customer satisfaction in Inanam Exchange / Mohd Salleh Mussawari - Mussawari, Mohd Salleh (2007)
A study on the TM Streamyx: Level of Customer Satisfaction in Inanam Exchange was conducted. The purposes of this study were to identify the factors influence customer decision to choose Streamyx, to access the general level of customer's satisfaction using Streamyx, to recommend strategic campaigns and promotion packages for Streamyx. The sampling used in this research is systematic sampling. The 63 respondents that interviewed are comprises TM Streamyx user. Data gathered from fieldworks was analyzed using statistical package of social science (SPSS).